Strategi Pengembangan Potensi Jayengan Kampung Permata Sebagai Kawasan Wisata Budaya di Surakarta - Josephin Fenatama Angel; Rina Kurniati (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Kampung Jayengan was formed in the early 19th century, when the royal family asked the jewelers from Martapura to come to Surakarta. Craftsmen were asked to make jewelry for the royal family in collaboration with Chinese ethnic gold entrepreneurs. They settled and married with local residents, so that cultural events took place such as the distribution of ‘Samin’ porridge and "Jarwana" cultural parade”. The Surakarta government established Jayengan as a creative economy industrial area. Constraints that occur: lack of tourism promotion, cultural events only once a year, lack of availability of raw materials, lack of internal support, competition with other industries. The purpose of the research is to make the strategy of tourism development. The study was conducted with interviews and questionnaires to identify activities, authentic values and tourist infrastructure. The identification results are made into a questionnaire variable and then processed into an External Internal Matrix (IE). IE Matrix for Jayengan readiness in cell I, handicraft products in cell IV. It can be concluded that the right strategy is Grow and Build with the development of tourist activities, authentic values and tourist infrastructure. The benefits of this study provide direction in developing strategies for urban villages as tourist destination.